Primary immunodeficiency disorders - Patel, Smita Y. (Henry Stewart Talks, 2020)
Introduction to Primary Immune Deficiencies (PIDs), The immune system function and PIDs, Disorders of innate immunity, Antibody deficiencies, T cell defects, PIDs early diagnosis and treatment